Workshop Pengembangan Bahan Ajar Matematika Bermakna Berbasis Peta Konsep bagi Guru Sekolah Dasar di Kabupaten Barru - Jafar Jafar; Damar Rais; Danial Danial; Norma Nasir; Abdul Majid (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2026)
The development of meaningful mathematics teaching materials remains a significant challenge in elementary schools, particularly in teachers’ ability to organize concepts systematically and contextually. One relevant strategy to support meaningful learning is the use of concept maps as cognitive tools. This community service program aimed to enhance elementary school teachers’ understanding and competence in Barru Regency in developing meaningful mathematics teaching materials based on concept maps through a structured workshop. The activity involved 30 teachers and was conducted through several stages: pretest, material presentation, discussion, hands-on practice in designing concept maps and teaching materials, posttest, and product evaluation. Data were collected using a comprehension test and a product assessment rubric, then analyzed using descriptive statistics, paired-sample t-test, and N-gain analysis. The results indicated a significant improvement in teachers’ understanding, with the mean score increasing from 62.4 on the pretest to 82.5 on the posttest. The paired t-test showed a significant difference (t = 11.27; p < 0.05), while the N-gain analysis revealed that 60% of teachers achieved high improvement and 40% moderate improvement. Product evaluation yielded an average score of 3.55 out of 4 (very good category), particularly in the structure of concept maps, interconnections among concepts, and alignment with elementary students’ characteristics. These findings suggest that concept map-based workshops are effective in improving teachers’ conceptual understanding and the quality of meaningful mathematics teaching materials, with potential as a sustainable professional development model.